2021
DOI: 10.1056/nejmoa2108453
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Sarbecovirus Neutralizing Antibodies in BNT162b2-Immunized SARS-CoV-1 Survivors

Abstract: Summary Emerging severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern pose a challenge to the effectiveness of current vaccines. A vaccine that could prevent infection caused by known and future variants of concern as well as infection with pre-emergent sarbecoviruses (i.e., those with potential to cause disease in humans in the future) would be ideal. Here we provide data showing that potent cross-clade pan-sarbecovirus neutralizing antibodies are induced in survivors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
166
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(178 citation statements)
references
References 25 publications
9
166
2
1
Order By: Relevance
“…We found that the strong pre-CRA group was more likely to produce higher antibody responses at some of the epitopes, such as S574-603 and S1106-1125. Consistent with previous evidence, vaccinees who were previously infected with SARS-CoV or SARS-CoV-2 had a significantly higher antibody response than previously uninfected vaccinees (37)(38)(39)(40)(41)(42). However, upon analysis of the global profiles of antibody responses to the S protein peptides, the strong pre-CRA and weak pre-CRA groups showed similar patterns in response to IgG or IgM antibodies.…”
Section: Discussionsupporting
confidence: 85%
“…We found that the strong pre-CRA group was more likely to produce higher antibody responses at some of the epitopes, such as S574-603 and S1106-1125. Consistent with previous evidence, vaccinees who were previously infected with SARS-CoV or SARS-CoV-2 had a significantly higher antibody response than previously uninfected vaccinees (37)(38)(39)(40)(41)(42). However, upon analysis of the global profiles of antibody responses to the S protein peptides, the strong pre-CRA and weak pre-CRA groups showed similar patterns in response to IgG or IgM antibodies.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, in such settings, it is conceivable that low selection stringency may allow rare precursor B cells, such as those leading to broadly neutralizing antibodies, to get selected ( 42 , 75 ). With SARS-CoV-2, the spike protein appears reasonably conserved across variants ( 76 ), and has allowed the design of vaccines that can generate antibodies with pan-sarbecovirus neutralizing activity ( 77 , 78 ). Thus, incorporating diverse antigens and inter-clonal competition are expected not to affect our qualitative inferences regarding SARS-CoV-2 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…To reach this target, our modelling results suggest that the vaccination programme would need to be extended to children aged 3-11 years, and vaccine efficacy against the infection would need to be >84%, in line with the efficacy estimated for the mRNA-1273 (Moderna) vaccine [9]. China is currently attempting to develop mRNA vaccines [55], vaccines that specifically target the Delta variant [56], multi-valent vaccines, and universal vaccines [57][58][59]. However, whether such vaccines will become available in the short term is unknown.…”
Section: Discussionmentioning
confidence: 77%
“…multi-valent vaccines, and universal vaccines [57][58][59]. However, whether such vaccines will become available in the short term is unknown.…”
Section: Discussionmentioning
confidence: 99%